Do Parenting Styles Influence Mental Toughness and Sportsmanship in Young Athletes? A Structural Equation Modelling Approach - Vega-Díaz, Marta; González-García, Higinio (Journal of Human Kinetics, 2025)
The goal of this research was to evaluate whether there are relationships between parenting styles, mental toughness, and sportsmanship in athletes. The sample was made up of 201 Spanish adolescent athletes (Mage = 15.30; SD = 1.82; 110 men and 91 women) who completed the Child-Parental Acceptance-Rejection Questionnaire, the Mental Toughness Inventory, and the Spanish version of the Multidimensional Sportsmanship Questionnaire. Structural equation modeling was used to examine the relationships among the studied variables. The results revealed that maternal and paternal love/affection significantly positively predicted mental toughness. Likewise, the results showed that paternal hostility/aggression and indifference/neglect significantly positively predicted fair play. In conclusion, given the connection between perceived parental education, psychological variables (mental toughness), and sports ethics principles (sportsmanship) of athletes, programs that train athletes' cognitive and axiological skills should not ignore the parental role. Hence, an attempt could be made to encourage athletes to compete when feeling mentally strong and respecting the ethical values of sportsmanship.
Keywords: parenting; sports; competitors; coaching; youngsters